Doping dependence of the electron–phonon and electron–spin fluctuation interactions in the high-Tc superconductor Bi2Sr2CaCu2O8+δ - Springer, D. (2014)
Using ultrafast optical techniques, we detect two types of bosons strongly coupled to electrons in the family of Bi2Sr2CaCu2O8+ (Bi-2212) from the underdoped to overdoped regimes. The different doping dependences of the electron–boson coupling strengths enable us to identify them as phonons and spin fluctuations: electron–phonon coupling ( e−ph) peaks at optimal doping, while electron–spin fluctuation coupling ( e−sf) decreases monotonically with doping. This observation is consistent with two facts: (i) superconductivity is in close proximity with antiferromagnetism at low dopings and (ii) a pronounced lattice renormalization effect at larger dopings.